Collaborative Governance in the Implementation of Regional Sports Design: Realizing Sustainable Sports Governance in East Java - Kurniawan, Aditya Wahyu Dwi; Mustofa, Amirul; Pramudiana, Ika Devy (PT. Anagata Sembagi Education, 2026)
This study examines the implementation of collaborative governance principles in the Regional Sports Design of East Java as a strategic approach to achieving sustainable and inclusive sports management. The application of collaborative governance involves multiple stakeholders, including local governments, the Indonesian National Sports Committee, the Indonesian National Paralympic Committee, the private sector, universities, and the broader community, in the formulation of adaptive and data-driven sports policies. This research analyzes five key dimensions starting conditions, institutional design, leadership, collaborative processes, and outcomes emphasizing the importance of inter-actor collaboration, capacity building among stakeholders, and transparency in decision-making. The findings indicate that effective collaboration among diverse actors enhances the equitable distribution of sports facilities, strengthens athlete development, and ensures the long-term sustainability of regional sports programs. Furthermore, this governance approach promotes inclusivity in disability sports by providing equal access for persons with disabilities to participate and compete at national and international levels. Overall, the study concludes that collaboration-based sports governance is essential for achieving sustainable, inclusive, and collectively beneficial outcomes in the long term